The myth of decline : the rise of Britain since 1945 / George L. Bernstein. - Bernstein, George Lurcy, 1947- (Vintage Digital, 2011)
This history of Britain since 1945 confronts two themes that have dominated British consciousness during the post-war era - the myth of decline and the pervasiveness of American influence.